Hermeneutics Study: Analysis of Denotative And Connotative Meaning in The Song Berita Kepada Kawan By Ebiet G. Ade - Suryanti; Harto Malik; Zaedun Naim; Everhard Markiano Solissa; Zarkasi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
The song is a sequence of beautiful words, often carrying meanings both connotative (figurative) and denotative (literal). This research aims to unveil the connotative and denotative meanings in the song â€œBerita Kepada Kawanâ€ by Ebiet G. Ade. The theoretical framework employed in this study is hermeneutic research. It is a qualitative study where the data consists of sentences containing connotative and denotative meanings, and the source of the data is the lyrics of the song